Tension entre indicateurs de production et indicateurs de sécurité - Catherine Fournier; Raouf Ghram; Tahar-Hakim Benchekroun; Francis Six (Activités)
Companies’ chief sources of concern are related to profitability issues. Most decide to obtain certification in order to maintain their operations, and this requires them to use indicators. Some research has shown how this approach can cause safety issues to be "forgotten".Our research took place in a firm based in Tunisia which in 2004 introduced a quality management system that resulted in certification. This was undertaken to comply with customer expectations and to keep the company in business.We will show here how the use of indicators can sometimes cause safety issues to be pushed aside. The problem of a gap between what the indicator shows about the business and what is actually happening in the workplace leads to decisions being taken that do not result in the improvement of working conditions.